Comparative Governance of Public and Private Nature-Based Sport Tourism Destinations in Banyumas, Indonesia - Nakhu Puji Leksana; Mohammad Hardi Wahyono; Ratananaphadol Smitinand; Masoud Karimzadeh (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to compare governance practices, managerial effectiveness, and development strategies between public and private sport tourism destinations in Banyumas Regency, Indonesia. The study specifically examines organizational management functions, governance characteristics, and strategic opportunities that support the sustainability and competitiveness of nature-based sport tourism destinations. Methodology: A qualitative descriptive design was employed at Palawi Risorsis and Baturaden Adventure Forest in Banyumas Regency, Central Java, Indonesia. Data were collected through structured interviews involving destination managers, operational staff, and tourists, complemented by direct observation and document analysis. The collected data were analyzed using thematic coding, comparative descriptive analysis, and SWOT analysis to identify managerial patterns and strategic development priorities. Main Findings: The findings revealed substantial differences in governance and management practices between the two destinations. Baturaden Adventure Forest demonstrated greater managerial flexibility, stronger sport tourism orientation, responsive evaluation mechanisms, and a family-oriented organizational culture. In contrast, Palawi Risorsis faced bureaucratic constraints, weaker supervision systems, and limitations in human resource capacity. SWOT analysis further identified seven strategic development directions to strengthen destination competitiveness, operational effectiveness, and long-term sustainability. Novelty/Originality of this study: This study provides one of the few comparative analyses of public and private governance models in Indonesian sport tourism destinations. The research advances existing knowledge by demonstrating how governance structures influence managerial effectiveness, organizational adaptability, and strategic decision-making. It also offers practical insights for policymakers and destination managers seeking to enhance the sustainability and competitiveness of nature-based sport tourism destinations in developing-country contexts.